Securities Market Regulation in Nepal: A Legal and Institutional Perspective - Bhandari, Sudip (KDCBAR Law Journal, 2025)
This study explores the legal and institutional framework governing the securities market in Nepal, emphasizing its significance in mobilizing capital, fostering investment, and promoting economic growth. It highlights the transformative role of the Securities Board of Nepal (SEBON) in regulating and modernizing the market through legal instruments such as the Securities Act, 2063, and complementary regulations including those on mutual funds, credit rating, depository services, and stock exchange operations. The research underscores key milestones in Nepal’s securities regulation, from the early Companies Act of 1936 to the establishment of NEPSE and the evolution of investor-friendly systems like C-ASBA and Meroshare. Despite notable progress, the study identifies persistent challenges: weak enforcement, overlapping institutional mandates, insufficient technical capacity, and legal gaps that hinder full market efficiency and investor protection. While recent reforms align with international standards, especially those of the WTO, the current regulatory framework remains inadequate to meet the demands of a rapidly evolving financial landscape. The paper concludes by advocating for comprehensive legal reforms, institutional strengthening, and enhanced governance mechanisms to develop a robust, transparent, and globally competitive securities market in Nepal.